High Air Stability and Excellent Li Metal Compatibility of Argyrodite‐Based Electrolyte Enabling Superior All‐Solid‐State Li Metal Batteries. (26th May 2022) - Liu, Hong; Zhu, Qisi; Wang, Chao; Wang, Guoxu; Liang, Yuhao; Li, Dabing; Gao, Lei; Fan, Li‐Zhen
Abstract: Sulfide solid electrolytes (SSEs) for all‐solid‐state Li metal batteries (ASSLMBs) are attracting increasing attention due to their ultrahigh ionic conductivity and good machinability. However, current SSEs generally suffer from inferior Li metal compatibility and poor air‐stability, which severely impede their practical applications for ASSLMBs. Herein, novel argyrodite‐based SSEs of Li6+2 x P1− x Bi x S5−1.5 x O1.5 x Cl are synthesized via the Bi, O co‐doping the Li6 PS5 Cl for the first time. By adjusting the concentrations of dopant, the optimized Li6.04 P0.98 Bi0.02 S4.97 O0.03 Cl presents an ultrahigh ionic conductivity (3.4 × 10 −3 S cm −1 ). Moreover, such electrolyte displays splendid structural stability after exposure to humid air and chlorobenzene, demonstrating admirable air‐stability and solvent‐stability. The mechanism of the enhanced air‐stability of oxide‐doped SSEs is profoundly understood by conducting first‐principles density functional theory calculations. In addition, the Li6.04 P0.98 Bi0.02 S4.97 O0.03 Cl electrolyte triggers the generation of LiBi alloy at the anode interface, which plays a crucial role in reducing Li + diffusion energy barriers and improving interfacial compatibility, leading to an ultrahigh critical current density of 1.1 mA cm −2 and splendid cyclic stability in Li symmetric cell. As a result, ASSLMBs equipped with either pristine or air‐exposed Li6.04 P0.98 Bi0.02 S4.97 O0.03 Cl can deliver satisfying discharge specific capacity at room temperature. Abstract : Argyrodite‐based electrolyte of Li6.04 P0.98 Bi0.02 S4.97 O0.03 Cl is synthesized successfully via Bi, O co‐doping the Li6 PS5 Cl for the first time. As‐prepared electrolyte exhibits high ionic conductivity, high air stability, and good Li metal compatibility. Moreover, either pristine or air‐exposed Li6.04 P0.98 Bi0.02 S4.97 O0.03 Cl can be used as a single electrolyte layer to enable all‐solid‐state Li metal batteries with superior electrochemical performance.